2011
DOI: 10.1177/00333549111260s118
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, Sprawl, and Restaurant Types Influence Body Mass Index of Residents in California Counties

Abstract: Objectives. This article examines the relationships between structural poverty (the proportion of people in a county living at 130% of the federal poverty level [FPL]), urban sprawl, and three types of restaurants (grouped as fast food, chain full service, and independent full service) in explaining body mass index (BMI) of individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Regarding substantive criteria, as a large number of classes may produce classes that are statistically but not practically different, and small class sizes may result in classes that are difficult to interpret meaningfully (Huang, 2012), we stopped adding classes when the smallest class size was less than 5% of the number of census tracts. Latent variable mixture modeling was conducted using Mplus 6.11 software (Muthen & Muthen, 1998-2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding substantive criteria, as a large number of classes may produce classes that are statistically but not practically different, and small class sizes may result in classes that are difficult to interpret meaningfully (Huang, 2012), we stopped adding classes when the smallest class size was less than 5% of the number of census tracts. Latent variable mixture modeling was conducted using Mplus 6.11 software (Muthen & Muthen, 1998-2011.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible applications of this method include examining different exposure risks linked to poor health and socio-demographic variation, such as alcohol and fast-food consumption Boone-Heinonen et al, 2011;Chartier & Caetano, 2010;Gregson, 2011). It is only through such a thoughtful approach that we will ensure the greatest impact for our investment in public health.…”
Section: Discussionmentioning
confidence: 99%
“…However, slightly more evidence exists supporting the latter. Studies by Gregson, Ingami, and colleagues and Mehata and colleagues both observed that access to fast food restaurants was associated with increased BMI [56, 65, 66]. Additionally, Morland and colleagues reported that the presence of convenience stores was associated with higher obesity prevalence [62].…”
Section: Food Retail Environment and Obesity Riskmentioning
confidence: 99%
“…Additionally, Morland and colleagues reported that the presence of convenience stores was associated with higher obesity prevalence [62]. Despite the studies yielding statistically significant results in the desired direction [51, 54, 56, 62, 6568], a fair percentage of studies observed null findings [52, 55, 57, 58, 6971]. Contrary to most findings, studies reporting unexpected or negative results also exist in the literature [49, 50, 55, 57].…”
Section: Food Retail Environment and Obesity Riskmentioning
confidence: 99%
See 1 more Smart Citation